POLITIK HUKUM PENGELOLAAN SUMBER DAYA ALAM DI INDONESIA - ANDY TONGGO MICHAEL SIHOMBING; RICKY BANKE (LP2MTBM MAKARIOZ, 2023)
Indonesia is part of a global community that has an obligation to conserve and manage its natural resources and environment, in addition to maintaining the sustainability of the function of natural resources for present and future generations and maintaining the survival of the nation, also to maintain climate stability and global environmental sustainability. Legal politics is the basic policy of state administrators in the field of law that will be, is being and has been in effect, originating from the values that apply in society to achieve the goals of the aspired state. In formulating and enacting laws that have been and will be carried out, of course legal politics will hand over legislative authority to administrators, provided that they still pay attention to the values prevailing in society. The output of all of this is directed towards achieving the desired goals of the State. The legal political portrait of natural resource management in Indonesia is framed through repressive legal policies, customary law/local law being neglected in the process of forming legislation, thus generating resistance from indigenous peoples in various regions of the country resulting in natural resource conflicts. The legal politics of natural resource management in the future must adhere to the ideology of legal pluralism, which respects and recognizes and accommodates access, interests, rights and wisdom of indigenous peoples in managing natural resources in Indonesia.